Inflammatory Activity Test of N-Hexant Extract of Kandis Acid (Garcinia Xanthochymus) Against Male White Mice (Rattus norvegicus) - Winata, Hanafis Sastra; Hafiz, Ihsanul; Kartika, Yulis; Sihombing, Delima (Budapest International Research and Critics University, 2021)
Kandis acid (Garcinia xanthochymus) belongs to the genus Garcinia plants scattered in the tropics of Asia. The fruit is widely used as a flavoring dish by the Malay people. Based on research that has been done on the genus Garcinia, it is known that the largest active compound is the santon group. The research used is experimental. The sample in this study was a male white mouse. Anti-inflammatory activity test was conducted on test animals divided into 5 groups, each amounting to 5 heads with suspension test group N-hexan extract of kandis acid fruit dose 200, 400, 800 mg/kg bb, negative control group is CMC Na 1% susspence and positive control is Na diclofenac 2.25 mg/kg bb. Observations were made for 6 hours then the data was analyzed with a one way annalissys of variance (ANOVA) test. Research showed kandis acid extract (Garcinia xanthochymus) was shown to provide anti-inflammatory effects in male white mice induced caragenan at a dose of 200 mg / kgbb with an average value of udem decrease of 5.25, 400 mg/kgbb with an average udem decrease of 5.17 and 400mg/kgbb with an average udem decrease of 6.08, with the most effective dose in anti-inflammatory reduction being 400 mg/kgbb. The most effective dose of candis acid extract (Garcinia xanthochymus) in anti-inflammatory reduction in male white mice was the dose of kandis acid extract (Garcinia xanthochymus) 400 mg/kgbb. It is recommended to the next researcher to conduct fractionation research on kandis acid fruit plants..Â Â